Cross-Domain Transfer Learning for PCG Diagnosis Algorithm - Tseng, Kuo-Kun; Wang, Chao; Huang, Yu-Feng; Chen, Guan-Rong; Yung, Kai-Leung; Ip, Wai-Hung (Biosensors (Basel), 2021)
Cardiechema is a way to reflect cardiovascular disease where the doctor uses a stethoscope to help determine the heart condition with a sound map. In this paper, phonocardiogram (PCG) is used as a diagnostic signal, and a deep learning diagnostic framework is proposed. By improving the architecture and modules, a new transfer learning and boosting architecture is mainly employed. In addition, a segmentation method is designed to improve on the existing signal segmentation methods, such as R wave to R wave interval segmentation and fixed segmentation. For the evaluation, the final diagnostic architecture achieved a sustainable performance with a public PCG database.